1999
DOI: 10.1007/s002560050522
|View full text |Cite
|
Sign up to set email alerts
|

Posteromedial corner of the knee: MR imaging with gross anatomic correlation

Abstract: The contrast-enhanced sequences and the coronal oblique images allowed for improved visualization of the structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 3 publications
0
32
0
4
Order By: Relevance
“…The sixth tendinous fibre bundle was found to insert at the lateral meniscus". In 1999, Loredo et al [27] concluded that there are "five arms of insertions, one being a principle attachment consisting of a series of slips of tendon". The principal or direct attachment was to the "tibial tubercle on the posterior aspect of the medial tibial condyle (just below the joint line)".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sixth tendinous fibre bundle was found to insert at the lateral meniscus". In 1999, Loredo et al [27] concluded that there are "five arms of insertions, one being a principle attachment consisting of a series of slips of tendon". The principal or direct attachment was to the "tibial tubercle on the posterior aspect of the medial tibial condyle (just below the joint line)".…”
Section: Resultsmentioning
confidence: 99%
“…In 2003, Beltran and Matityahu [2] explained the normal anatomy of the SMTU quite similarly to Kim et al [21] "The distal semimembranosus tendon divides into five tendinous branches or arms at approximately the level of the joint line: the anterior or tibial arm, the direct arm, the inferior or popliteal arm, the capsular arm, the oblique popliteal ligament" [27]. This article further describes the expansions as follows: "The anterior or tibial arm, also known as the reflected arm, extends anteriorly passing under the posterior oblique ligament and inserts in the medial aspect of the proximal tibia under the tibial collateral ligament.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). 9,[83][84][85] The capsule proper, the deepest of the 3 layers, attaches to the medial meniscus and to the articular margins. Anatomic descriptions of the medial side of the knee describe the MCL as having an anterior vertical component and a posterior oblique component (see Fig.…”
Section: Posteromedial Corner Of the Knee Anatomy Biomechanics And mentioning
confidence: 99%
“…Its distal attachment lies deep to the semitendinosus and gracilis tendons. 83,85,87,88 The intermediate layer (II) and the deeper capsule proper (III) unite posteriorly with the anterior margin of the superficial MCL and the PMC of the knee. The posterior portion of the MCL originates at the proximal attachment of the medial collateral ligament and extends distally in a posterior oblique fashion (at 25 with respect to the anterior vertical portion) to reach the posteromedial aspect of the knee, forming an envelope about the semimembranosus tendon.…”
mentioning
confidence: 99%